The use of controlled human infection models to identify correlates of protection for invasive Salmonella vaccines - McCann, Naina; Paganotti Vicentine, Margarete; Kim, Young Chan; Pollard, Andrew J. (Frontiers in Immunology, 2024)
Controlled human infection model (CHIM) studies, which involve deliberate exposure of healthy human volunteers to an infectious agent, are recognised as important tools to advance vaccine development. These studies not only facilitate estimates of vaccine efficacy, but also offer an experimental approach to study disease pathogenesis and profile vaccine immunogenicity in a controlled environment, allowing correlation with clinical outcomes. Consequently, the data from CHIMs can be used to identify immunological correlates of protection (CoP), which can help accelerate vaccine development. In the case of invasive Salmonella infections, vaccination offers a potential instrument to prevent disease. Invasive Salmonella disease, caused by the enteric fever pathogens Salmonella enterica serovar Typhi (S. Typhi) and S. Paratyphi A, B and C, and nontyphoidal Salmonella (iNTS), remains a significant cause of mortality and morbidity in low- and middle-income countries, resulting in over 200,000 deaths and the loss of 15 million DALYs annually. CHIM studies have contributed to the understanding of S. Typhi infection and provided invaluable insight into the development of vaccines and CoP following vaccination against S. Typhi. However, CoP are less well understood for S. Paratyphi A and iNTS. This brief review focuses on the contribution of vaccine-CHIM trials to our understanding of the immune mechanisms associated with protection following vaccines against invasive Salmonella pathogens, particularly in relation to CoP.